Komunikasi Keluarga Dalam Islam: Studi Peran Parenting Islami Orang Tua Dan Anak Dalam Era Digital - Kamila, Suci Nur; Febrianti, Nadia; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The digital era has brought significant changes in communication patterns within families, where information and communication technology (ICT) is now an inseparable part of everyday life. In this context, the application of Islamic parenting principles is very crucial to maintain harmony and the quality of communication between family members. In Islamic teachings, family communication has a very important role and is regulated by principles derived from the Qur'an and Hadith. Good communication in the family is not just an exchange of information, but also a means to build a sakinah, mawaddah, and rahmah family, namely a family that is calm, full of love, and affection. This study uses a qualitative approach by analyzing the role of Islamic parenting between parents and children in the digital era. The results of the study show that Islamic parenting principles emphasize the importance of effective, loving, and religiously based communication. In today's digital era, it is important for parents to have a deep understanding of technology and its impact on children. In addition, they also need to develop adaptive communication skills to face the various challenges that arise from the use of technology, such as cyberbullying, social media addiction, and exposure to negative content. In the context of Islamic parenting, effective communication between parents and children is the key to building strong, trusting, and supportive relationships. Islamic parenting principles play an important role in guiding communication patterns in families in this digital era. By implementing these values, parents can create a harmonious and loving family atmosphere, remain in accordance with religious teachings, and be ready to face the various challenges posed by technological developments.